Analog to Digital Converter sebagai Antarmuka Sistem - Eddy Nurraharjo; Edy Winarno (Jurnal Ilmiah Dinamika Teknik, 2008)
Previous researches have unfolded some technical improvements on system automation which uses an integrated control system with its own unique intelligence in solving different complicated problems in which the system is applied An obstacle (requenl/y encountered is the development o}' a micro control i/ller/ace on several transducer characteristics which can provide an early detection on a certain condition to perform a further instruction. Transducer, which is the outer end terminal of a control system, needs a distinct analysis on its own characteristics in order to decide the most appropriate interface model to help the control system perfÒrm an execution on the basis of the environmental changes to be detected. Several transducer output characteristics also need a specific synchronization for the microcontroller input terminal, such as the synchrony between the electrical current _and the voltage of the input terminal. Thus, the researchers conducted an analysis on the general characteristics of the MCS51-based control system interface as the transducer series input terminal